La demanda externa de uvas frescas de Perú, 1994-2015 - Pecho Esteban, Luis Alberto (2016)
This research work had as its central objective is to analyze the determinants of external demand for fresh grapes from Peru during the period 1994-2015. Regarding the research design it has opted for an approach of longitudinal, descriptive and non-experimental cutting, for which the information collected in the theoretical framework was used. To reach the results econometric research was conducted the following variables were included: the demand amount of fresh grapes from Peru (Qd) - measured by the export of fresh grapes - the price of global fresh grapes (PM) , the world price of fresh strawberry (PMF), the world price of tomatoes (PMT), the per capita income of the United States (YPUSA) per capita in the Netherlands (YPHOL) income - as both countries are the most representative to occupy 43% and 72% of exports of Peruvian fresh grapes. When performing regression model had to exclude variables per capita income and other relative prices for the US, because were not statistically significant in applied models and add the variable trend (TREND @ ^ 0.75) to remove the natural tendency of the data and better appreciate the relationship between the dependent variable and independent variables. Finally, foreign demand for fresh grapes is an inelastic good in both countries export more participation. Elasticities of demand variables are: -0,971 in the relative price of grapes for USA, -0935 in the relative price of grapes for the Netherlands, 0.81 in the relative price of strawberry Netherlands (substitute good) and - 0.45 in the relative price of tomatoes for the Netherlands ( complementary good).